Unraveling p-Cresol: from biosynthesis to biological and biochemical activities - Zhang, Ying; Xu, Xinfang; Fan, Xiaona; Wu, Yuting; Zhang, Xiufang; Wu, Yingxue; Li, Xiangri; Zou, Qinwen (Frontiers in Pharmacology, 2025)
p-Cresol, a ubiquitous low-molecular-weight volatile phenolic compound, permeates the vicinity of human, plant, and animal ecosystems through complex biosynthetic pathways and environmental exposure routes. Beyond its well-documented toxicity and metabolic interference, emerging evidence reveals its paradoxical roles as a pivotal signaling molecule in diverse ecological and biological systems. In the context of emerging research on the intricate interplay between chemical substances and life processes, its multifaceted biological and biochemical activities have become a focal point of interdisciplinary exploration. This comprehensive review systematically dissects the latest advancements in p-cresol research, meticulously tracing its biosynthesis pathways. Beyond its well-documented pungent odor and toxicity thresholds, the review delves into the cutting-edge discoveries of p-cresol’s potential as an antioxidant and modulator of glucose homeostasis. Notably, the discussion on p-cresol removal strategies includes modulating the microbiota, optimizing diet and improving activated charcoal adsorption. By bridging the gaps between basic research and practical applications, this review not only provides a holistic understanding of p-cresol’s dual-edged nature but also offers strategic guidance for developing safer and more efficient p-cresol utilization models while mitigating its health risks, ultimately guiding precision probiotic interventions for gut microbiota modulation (to lower endogenous p-cresol production) and targeted clinical trials for metabolic disorder management (e.g., chronic kidney disease-related p-cresol accumulation).